The Redox Potential Measurements for Heme Moieties in Variants of D-Fructose Dehydrogenase Based on Mediator-assisted Potentiometric Titration - Yohei SUZUKI; Keisei SOWA; Yuki KITAZUMI; Osamu SHIRAI (Electrochemistry, 2021)
The effect of mutation on the redox potentials (E°′) of the heme moieties in the variants of d-fructose dehydrogenase (FDH) was investigated by mediated spectroelectrochemical titrations. The replacement of the axial ligand of heme from methionine to glutamine changes the E°′ value more negatively than that of the corresponding heme moiety in the recombinant (native) FDH (rFDH). The determined E°′ values of non-targeted heme moieties in the variants were also shifted in a negative direction from that in rFDH. Thus, enzyme modification changes E°′ of the heme moieties in unmodified protein regions.